ChemInform Abstract: Synthesis of Highly Functionalized 4‐Aminoquinolines. Issue 28 (June 2016) - Wezeman, Tim; Zhong, Sabilla; Nieger, Martin; Braese, Stefan
Abstract: Highly functionalized quinolines are prepared from N‐aryl amides and sulfonyl ynamides.